Inovasi Tanda Jeda Baru pada Mushaf al-Qur’an: Studi Pergeseran dari Nilai Fungsional ke Nilai Komersial pada Mushaf Waqf-Ibtidā’ - Al Insyirah, Sofia Mawaddah (Contemporary Quran, 2024)
The growing demand for the printed copy of the Quran, addressed by publishers through various innovations such as the introduction of new pause marks, reflects a shift from use value to commercial value. This study aims to demonstrate this shift by examining how new pause marks are determined. Employing a qualitative method, the research utilizes the qualitative comparative analysis (QCA) model for data analysis. The study reveals differences in the purpose behind implementing new pause marks in waqf-ibtidā’, primarily due to deviations from the syntactical relationships upheld in standard waqf-ibtidā’ rules. A consistent pattern of separation between elements such as fi’il and fā’il, mubtadā’ and khabr, and al-ḥāl and ṣāḥib al-ḥāl is observed. This separation caters to aesthetic considerations, purportedly to accommodate new Qur'an readers who might have shortness of breath. Such a purpose points to the marketing-oriented image-building of waqf-ibtidā’, aiming to facilitate ease in finding stopping points. However, this emphasis on convenience often leads to the distortion of meaning, as it interrupts the linguistic coherence, making the text harder to understand. The focus on innovations that enhance marketability highlights a form of commodification that overlooks the traditional use value of the Qur'an. This shift from use value to commercial value underscores a trend among producers of the printed copy of Quran of waqf-ibtidā’ to place the Quran within an industrial context that promotes religion’s presence in the public sphere.